Double ligation is useful to prevent recurrence for paediatric inguinal hernia in the laparoscopic percutaneous extraperitoneal closure procedure. Issue 2 (22nd March 2021) - Ohba, Go; Takahashi, Ryo; Okada, Naoki; Minato, Masashi; Nakayama, Masato; Yamamoto, Hiroshi
Abstract: Aim: Although laparoscopic percutaneous extraperitoneal closure (LPEC) is the standard procedure for paediatric inguinal hernia repair in our country, recurrence is an important problem. In this study, we examined the usefulness of double ligation in preventing recurrence in the LPEC procedure. Methods: We retrospectively examined children with inguinal hernias who underwent the LPEC procedure. Cases from October 2012 to June 2016 who underwent surgery for inguinal hernias with single ligation were defined as Group A. Children operated on from July 2016 to April 2019, when double ligation was the standard procedure in our institution, were defined as Group B. We reviewed the operative time and postoperative complications including recurrence rate. Double ligation was performed by holding two threads on the LPEC needle and then binding them individually. Results: Group A consisted of 401 patients and Group B consisted of 360 patients. No significant differences were noted between the groups with respect to operative time, infection, metachronous contralateral hernia or testicular atrophy. The recurrence rate was significantly higher in Group A with recurrence occurring in seven cases compared to none in Group B. Conclusions: Double ligation in the LPEC procedure is useful for preventing recurrence.